Anglo-Chinese encounters since 1800 : - Wang, Gungwu (Cambridge University Press, 2003)
Wang Gungwu's study of the relationship between China and the Chinese with imperial Britain examines the possibilities, as well as the limits of their encounters. Beyond the clichés of opium, fighting, and the diplomatic skills needed to fend off rivals and enemies, Gungwu probes areas of more intimate encounters, not least of which is the beginning of a broader English-speaking future between the two countries